STRATEGI PENGEMBANGAN UMKM PADA DESTINASI SUMBER GEMPONG TRAWAS DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT LOKAL KAWASAN WISATA - Olinda Octavia (PT. Habe Cendekia Utama, 2025)
This study aims to explain the strategies used in developing SMEs at the Sumber Gempong destination and to identify the determinants of SME development at the Sumber Gempong destination. This research is qualitative research with a descriptive research type. This type of research is a method in which the study is conducted using descriptive data in the form of written language or observations, which are used by the researcher and sourced from the oral information of informants who are the subjects of this study. The sample size in this study is 23 informants to obtain data related to the research. The results obtained in this study indicate that MSMEs in the Sumber Gempong tourist destination have a positive impact on the economic growth of the local community in the tourist area. This can also be evidenced by the village's contribution to regional revenue (PAD) in 2022, which reached Rp. 681,514,229. This represents a significant achievement made by the village authorities in collaboration with their community to jointly pursue better economic growth. This study provides recommendations to the relevant government authorities to improve the quality of various facilities so that they can continue to support the existence of tourist destinations, enabling MSME actors in the destination areas to carry out various product innovations by introducing local products that are the village's leading subsector to increase the attractiveness for visitors.